Kesan latihan menggunakan pendekatan metakognitif dan penyoalan strategik dalam menyelesaikan masalah matapelajaran fizik - Alex Pega, Anak Mahda. (Universiti Malaysia Sarawak (UNIMAS), 2003)
The purpose ofthis research was to study the effects oftraining using metacognitive approach and strategic questioning in solving Physic problem. The dependent variable in this study was students achievement while the independent variable was the training given to the students. This research was an experimental design research where the students were divided into two groups, experimental and control group. Students achievement was measured by finding the mean difference between students mark during pn!test and posttest in both group. For the conclusion, it was found that training using metacognitive approach and strategic questioning can help student to improve their performance in solving Physic problem. This was based on thefindingfrom the study that showed student in the experimental group achieved higher mark compared to students in the control group.